Pengaruh Efikasi Diri, Minat Kerja, Bimbingan Karir Terhadap Kinerja Bripka Polres Lebak - Yumhi Yumhi (The Asia Pacific Journal Of Management Studies, 2022)
This study analyzes the effect of self-efficacy on performance by focusing on self-efficacy factors that affect performance related to its contribution to organizational goals. Then this study analyzes the effect of work interest on performance by focusing on the factors of work interest that affect performance related to its contribution to organizational goals. Furthermore, this study analyzes the effect of career guidance on performance by focusing on career guidance factors that affect performance related to its contribution to organizational goals. To see the extent to which these factors have an effect, the researchers conducted a research analysis together so that it would be seen how much these factors influenced behavior in the organization.